INFORMATION ABOUT AUTHORS - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2014)
ROBERTAS BARTAŠEVIČIUS – PhD student of Social Sciences (Education) of the Education Department, Vilnius University. Research interests: education policy. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: robertas.bartasevicius@fsf.stud.vu.ltLILIJA DUOBLIENĖ – Doctor of Social Sciences (Education), Professor and the Head of the Education Department, Vilnius University. Research interests: education philosophy, education policy, multicultural education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: lilija.duobliene@fsf.vu.ltPLACIDA JASIŪNAITĖ – kindergarten teacher. Research interests: preschool education, moral values, education in games. Address: 17 Liubarto Str., LT-08118 Vilnius, Lithuania; e-mail address: jasiunaiteplacida@yahoo.comANTANAS KAIRYS – Doctor of Social Sciences (Psychology), Lecturer at the Department of General Psychology, Vilnius University. Research interests: time psychology, career psychology, personality traits. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: antanas.kairys@fsf.vu.ltSIMONA KONTRIMIENĖ – PhD student of Social Sciences (Education) of the Education Department, Vilnius University. Research interests: spirituality, education of spirituality, parenting, English for specific purposes (psychology), psycholinguistics. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: simona.kontrimiene@uki.vu.ltASTA KRIKŠČIŪNAITĖ – Master in Arts Teacher Training, Assistent of the Department of Music Pedagogy of the Faculty of Arts, Šiauliai University and the Doctoral Student in Education at Šiauliai University. Research interests: music education, assessment of progress and attainments. Address: 25 P. Višinskio Str., LT-76351 Šiauliai, Lithuania; e-mail: astakrisciunaite@yahoo.comARŪNAS LAURINAITIS – Member of the Board of Kaunas University of Technology, Vice-President of the Lithuanian Confederation of Industrialists. Address: 8 Vienuolio Str., LT-01104 Vilnius, Lithuania; e-mail address: arunas.laurinaitis@lpk.ltAUDRONĖ LINIAUSKAITĖ – Doctor of Social Sciences (Psychology), Professor at the Department of Psychology, Klaipėda University. Research interests: psychological time, career psychology, psychological well-being. Address: 5 S. Nėries Str., LT-92227 Klaipėda, Lithuania; e-mail address: audrone.liniauskaite@gmail.comEUGENIJUS NAZELSKIS – Doctor of Social Sciences (Education), Professor at the International Business School at Vilnius University. Research interests: professional orientation, human resource management. Address: 22 Saulėtekio Ave., LT-10225 Vilnius, Lithuania; e-mail address: e.nazelskis@gmail.comZITA NAUCKŪNAITĖ – Doctor of Social Sciences (Education), Associate Professor at the Department of Lithuanian Language and Literature Didactics, Lithuanian University of Educational Sciences. Research interests: argumentation theory, rhetoric, 31 Ševčenkos Str., LT-03111 Vilnius, Lithuania; e-mail address: zita.nauckunaite@leu.ltBIRUTĖ POCIŪTĖ – Doctor of Social Sciences (Psychology), Associate Professor at the Department of General Psychology, Vilnius University. Research interests: educational psychology, psychology of career choice, learning. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: birute.pociute@fsf.vu.ltJO RITZEN – Doctor of Philosophy (PhD), honorary professor of Maastricht University, former Dutch Minister of Education and Science, former Vice-President of the World Bank’s Development Economics Department and President of Universitet Maastricht. Research interests: higher education management, economics and finance. Address: Keizer Kareplein 19, 6211 TC Maastricht, the Netherlands; e-mail address: ritzen@merit.unu.eduDIANA STRAKŠIENĖ – Doctor of Social Sciences (Education Science), Professor, Head of the Department of Music Pedagogy of the Faculty of Arts, Šiauliai University. Research interests: music education, reflection of music, music therapy. Address: 25 P. Višinskio Str., LT-76351 Šiauliai, Lithuania; e-mail: dianastraksiene@gmail.comMARIA TILK – Doctor of Social Sciences (Education), Associate Professor at the Department of Educational Sciences, Tallinn University. Research interests: history of education, narrative. Address: 5 Uus-Sadama Str. Tallinn 10120, Estonia; e-mail address: maria.tilk@tlu.eeIEVA URBANAVIČIŪTĖ – PhD, Lecturer at the Department of Psychology Didactics, Lithuanian University of Educational Sciences. Research interests: career psychology, work psychology, learning and work motivation. Address: 39 Studentų Str., LT-08106 Vilnius, Lithuania; e-mail address: ieva.urbanaviciute@gmail.comVITA VENSLOVAITĖ – Doctor of Social Sciences (Education), Lecturer at the Department of Education, Vilnius University. Research interests: philosophy of education, musical education, phenomenology in education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: vitavensl@gmail.comRIMANTAS ŽELVYS – Habilitated Doctor of Social Sciences (Education), Professor at the Department of Education, Vilnius University. Research interests: education policy, education management, higher education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: rimantas.zelvys@leu.ltIRENA ŽUKAUSKAITĖ – Doctor of Social Sciences (Psychology), Lecturer at the Department of Clinical and Organizational Psychology, Vilnius University. Research interests: Personnel Psychology, Psychological Assessment. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: irena.zukauskaite@ fsf.vu.lt